Status kesehatan oral dan asupan zat gizi berhubungan dengan status gizi lansia - Akhdrisa Mura Wijaya; I Dewa Putu Pramantara; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Central Bureau of Statistics data in 2006, showed that the average life expectancy of the population living in Yogyakarta (DIY) was 73 years, and 73.8 years for those living in Sleman. This was higher than the average national life expectancy of 68.5 years. National Health Survey in 2007 showed that the prevalence of oral and dental problems in DIY was 23.6%, while the pulp and periapical tissue diseases in the elderly in Sleman districts was approximately 1704 cases. Hence, it was classified as one of the 10 most prevalent diseases in Public Health Centre. In addition, there were 406 older adults who were underweight.Objectives: To investigate the relationship between oral health status, nutrient intake and nutritional status in older adults.Methods: This study is an observational study with cross sectional design. Subjects were 310 patients aged 60-74 years old in Sleman district. Data obtained by interview, examination of the oral health status, measurement of body weight and arm span. Data were analyzed with Chi-square test.Results: There was a significant association between oral health status and protein intake (RP=2.38; 95%CI:1.42-3.970). Energy, fat and carbohydrates intake were not associated with oral health status (p>0,05). Nutritional status was significantly associated with the intake of the energy (RP=2.98, 95%CI:1.58-5.58), protein (RP=2.44, 95%CI:1,05-5.67), fat (RP=3.68, 95%CI:1.93-7.03) and carbohydrates (RP=4.89, 95%CI:2.54-9.4). However, there were no relationship found between oral health and nutritional status (RP=1.79, 95%CI:0.94-3.43.)Conclusion: There was a significant association between oral health status and protein intake. The intake of nutrients (energy, protein, fat, and carbohydrate) was significantly associated with nutritional status. However, there was no significant relationship found between oral health and nutritional status in older adults.